Culture shock and student engagement - Deborah Swallow; Barry Tomalin (Peoples' Friendship University of Russia (RUDN University), 2022)
This paper explores research into how to get foreign students studying overseas engaged with their work and how to deal with psychological difficulties in their new environment which can affect the quality of their studies. The paper is based on a presentation to HEURO (The Association of Higher Education European Officers) at a conference on the topic of Re-imagining Mobility for the Post-Pandemic World. The paper discusses how our understanding of international cultures needs to change, the difficulties faced by foreign students settling into another country, the impact of culture shock and how to deal with it and how to manage when faced with reverse culture shock when returning to your own country.